The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7575/aiac.ijalel.v.6n.1p.275
|View full text |Cite
|
Sign up to set email alerts
|

Grammar and Gender: A Comparative Study of the Integration and Organisation of Meanings in Selected Male and Female-authored Proseworks

Abstract: Studies have established gender-based variations in human’s use of language, particularly in the areas of grammar and lexis.  This study investigated language use in prose-works involving male and female writers, aimed at finding out whether there were grammar related variations in the use of language by the selected male and female writers.  The framework adopted for analysis was the Hallidayan notion of Clause Complexes and Embedded Clauses and how writers made conscious choices from the grammar of logical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…O'Kearny & Dadds [8] analyzed language differences across genders in adolescent years. Combined with Hallidayan clause complex analysis, Dahunsi [9] found that men are syntactically and semantically complex, while women are syntactically and semantically simplex.…”
Section: Introductionmentioning
confidence: 99%
“…O'Kearny & Dadds [8] analyzed language differences across genders in adolescent years. Combined with Hallidayan clause complex analysis, Dahunsi [9] found that men are syntactically and semantically complex, while women are syntactically and semantically simplex.…”
Section: Introductionmentioning
confidence: 99%